Toponyms from Appellative Personal Names in the Southern Highlands Region - Mickienė, Ilona; Baranauskienė, Rita (Respectus Philologicus, 2019)
The aim of this article is to discuss the formation of toponyms derived from various kinds of appellatives originating from personal names of the southern part of Lithuania – South Highlands (Lith. Pietų Aukštaitija). This is one of the semantic groups of toponyms, differentiating in specificity and meaning from the base words (toponyms consist of appellative personal names). Research into toponyms of appellative personal names reveals how proper names reflect the worldview of the residents of the aforementioned region. The material for the article was collected from the geoinformation data base of Lithuanian toponyms (LVvGDB). To explain the origin of toponyms with reference to the base words, the dictionary of Lithuanian surnames (Lith. LPŽe), the dictionary of the Lithuanian language (Lith. LKŽe), geoinformation data base of Lithuanian toponyms (LVvGDB) were employed. Focusing on word-formation under the structural-grammatical classification of hydronyms developed by Aleksandras Vanagas, the toponyms of each group are divided into primary and secondary. Ethnonyms are classified as primary, derivatives, composites and compounds.